Healthy eating and reduced risk of cognitive decline: A cohort from 40 countries. (2nd June 2015) - Smyth, Andrew; Dehghan, Mahshid; O'Donnell, Martin; Anderson, Craig; Teo, Koon; Gao, Peggy; Sleight, Peter; Dagenais, Gilles; Probstfield, Jeffrey L.; Mente, Andrew; Yusuf, Salim
Abstract : Objective: We sought to determine the association of dietary factors and risk of cognitive decline in a population at high risk of cardiovascular disease. Methods: Baseline dietary intake and measures of the Mini-Mental State Examination were recorded in 27, 860 men and women who were enrolled in 2 international parallel trials of the ONTARGET (Ongoing Telmisartan Alone and in Combination with Ramipril Global Endpoint Trial) and TRANSCEND (Telmisartan Randomised Assessment Study in ACE Intolerant Subjects with Cardiovascular Disease) studies. We measured diet quality using the modified Alternative Healthy Eating Index. Cox proportional hazards regression was used to determine the association between diet quality and risk of ≥3-point decline in Mini-Mental State Examination score, and reported as hazard ratio with 95% confidence intervals with adjustment for covariates. Results: During 56 months of follow-up, 4, 699 cases of cognitive decline occurred. We observed lower risk of cognitive decline among those in the healthiest dietary quintile of modified Alternative Healthy Eating Index compared with lowest quintile (hazard ratio 0.76, 95% confidence interval 0.66–0.86, Q5 vs Q1). Lower risk of cognitive decline was consistent regardless of baseline cognitive level. Conclusion: We found that higher diet quality was associated with a reduced risk of cognitive decline. Improved diet quality represents an important potential target for reducing the global burden of cognitive decline.